Fundamentals of world regional geography - Hobbs, Joseph J. (Brooks/Cole,Cengage Learning, 2013)
Presents interactive learning, study, and exam preparation tools along with comprehensive text content for one semester/quarter courses. This title helps you understand the eight world regions, including the historical, cultural, economic, political, and physical aspects that create regional unity, give them personality, and make them newsworthy.